The Effect of Providing Classic Music Therapy to Reduce Anxiety in Pre-Operative Caesarea Sectio Patients - Mulyono, Tri; Novitasari, Dwi; Burhan, Asmat (Indonesian Journal of Global Health Research, 2024)
Anxiety, characterized by feelings of unease, apprehension, and physiological reactions, is a common issue for patients facing surgery. Music therapy, which utilizes musical elements to promote well-being, has been proposed as a method to alleviate anxiety. This study aims to evaluate the effect of classical music therapy on anxiety levels in patients scheduled for cesarean section at Charitas Hospital Palembang. The study employed a pre-experimental design with a one-group pretest-posttest approach. The population included all patients undergoing preoperative care over the past three months, averaging 122 patients. A purposive sampling technique was used to select 40 participants, exceeding the required sample size of 30 to anticipate potential dropouts. The instrument used was the APAIS scale, with its validity and reliability confirmed through preliminary testing. Data were analyzed using univariate and bivariate methods, with statistical processing conducted using SPSS for Windows. The results indicated that the majority of participants were in early adulthood (26–35 years old), classified as ASA II (80%), had a high school education, and were predominantly housewives (50%). Before therapy, the mean anxiety score was 19.90, which decreased to 15.70 after the intervention. A paired t-test showed a significant reduction in anxiety (p < 0.05), suggesting that classical music therapy is effective in reducing preoperative anxiety in cesarean section patients.